Weight-loss-independent benefits of exercise on liver steatosis and stiffness in Japanese men with NAFLD - Sechang Oh; Takehiko Tsujimoto; Bokun Kim; Fumihiko Uchida; Hideo Suzuki; Seiichiro Iizumi; Tomonori Isobe; Takeji Sakae; Kiyoji Tanaka; Junichi Shoda (JHEP Reports, 2021)
Summary: Background & Aims: A weight-loss-independent beneficial effect of exercise on non-alcoholic fatty liver disease (NAFLD) management has been reported, but the underlying mechanism is unknown. To help determine this mechanism, the effects of exercise on individual tissues (liver, adipose tissue, and skeletal muscle) were retrospectively studied. Methods: Data from Japanese obese men with NAFLD in a 3-month exercise regimen were analysed and compared with those in a 3-month dietary restriction program designed to achieve weight loss. The underlying mechanism was studied in a smaller subcohort. Results: Independent of the effect of weight loss, the exercise regimen reduced liver steatosis by 9.5% and liver stiffness by 6.8% per 1% weight loss, and resulted in a 16.4% reduction in FibroScan-AST score. Improvements in these hepatic parameters were closely associated with anthropometric changes (reduction in adipose tissue and preservation of muscle mass), increases in muscle strength (+11.6%), reductions in inflammation and oxidative stress (ferritin: -22.3% and thiobarbituric acid: -12.3%), and changes in organokine concentrations (selenoprotein-P: -11.2%, follistatin: +17.1%, adiponectin: +8.9%, and myostatin: -21.6%) during the exercise regimen. Moreover, the expression of target genes of the transcription factor Nrf2, an oxidative stress sensor, was higher in monocytes, suggesting that Nrf2 is activated. Large amounts of high-intensity exercise were effective at further reducing liver steatosis and potentiating improvements in pathophysiological parameters (liver enzyme activities and organokine profiles). Conclusions: The weight-loss-independent benefits of exercise include anti-steatotic and anti-stiffness effects in the livers of patients with NAFLD. These benefits seem to be acquired through the modification of inter-organ crosstalk, which is characterised by improvements in organokine imbalance and reductions in inflammation and oxidative stress. Lay summary: We investigated the effects of exercise on non-alcoholic fatty liver disease (NAFLD) that were not related to weight loss. We found that exercise had considerable weight-loss-independent benefits for the liver through a number of mechanisms. This suggests that exercise is important for NAFLD patients, regardless of whether they lose weight.